2012
DOI: 10.1055/s-0032-1305097
|View full text |Cite
|
Sign up to set email alerts
|

Geschlechtsunterschiede in der multimodalen Therapie depressiver Störungen mit komorbider Schmerzsymptomatik

Abstract: Women with a depressive disorder and chronic pain benefit significantly more from a CBT-orientated multimodal treatment and exhibit a considerably greater reduction of depressive symptoms than do men. These distinctions are not due to differences in received antidepressant medication, psychiatric comorbidities or educational background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This may be significant, given men have been found to experience significantly poorer premorbid and social functioning (Goldstein and Link, 1988), more pervasive neurodevelopmental abnormalities (Nopoulos et al, 1997), earlier illness onset (Häfner, 2003), are typically less emotionally expressive in response to external stimuli (Kring & Gordon, 1998), and to be more likely to experience extra-pyramidal side effects (Smith, 2010), all of which may impact treatment response in negative symptoms. However, while there is some evidence to suggest that women respond better to antipsychotic treatment (Abel et al, 2010; Usall et al, 2007), and CBT-orientated treatment for depressed patients with chronic pain (Pieh et al, 2012), we could find no studies examining the impact of gender on treatment response in group psychosocial interventions for schizophrenia. While there is some evidence to suggest that negative symptoms are both more severe and more prevalent in males (Galderisi et al, 2012; Morgan et al, 2008), a number of other studies have found no differences between the sexes (see Ochoa et al, 2012), suggesting that negative symptoms remain a significant issue for both men and women.…”
Section: Introductionmentioning
confidence: 82%
“…This may be significant, given men have been found to experience significantly poorer premorbid and social functioning (Goldstein and Link, 1988), more pervasive neurodevelopmental abnormalities (Nopoulos et al, 1997), earlier illness onset (Häfner, 2003), are typically less emotionally expressive in response to external stimuli (Kring & Gordon, 1998), and to be more likely to experience extra-pyramidal side effects (Smith, 2010), all of which may impact treatment response in negative symptoms. However, while there is some evidence to suggest that women respond better to antipsychotic treatment (Abel et al, 2010; Usall et al, 2007), and CBT-orientated treatment for depressed patients with chronic pain (Pieh et al, 2012), we could find no studies examining the impact of gender on treatment response in group psychosocial interventions for schizophrenia. While there is some evidence to suggest that negative symptoms are both more severe and more prevalent in males (Galderisi et al, 2012; Morgan et al, 2008), a number of other studies have found no differences between the sexes (see Ochoa et al, 2012), suggesting that negative symptoms remain a significant issue for both men and women.…”
Section: Introductionmentioning
confidence: 82%
“…[13] The difference in cognitive vulnerability to hopelessness seen in women could account for a poorer outcome to psychotherapy. [1516] Other researchers have similarly argued that female patients benefit more from an approach that considers external pressures. [3233] This is in keeping with our finding of women having a more negative inferential attitude toward negative life events, which is stable and global.…”
Section: Discussionmentioning
confidence: 99%
“…[14] Previous researchers have shown women to have poorer outcomes in psychotherapy when compared with their male counterparts, whereas others have shown that men have a poorer outcome. [1516] Cuijpers et al , on the other hand, have found gender to have no predictive role in response to psychotherapy. [17] Joshi claims that given the patriarchal nature of Indian society, there is a strong need for integrating gender discourse within existing counseling services in India.…”
mentioning
confidence: 99%
“…For example, while one cohort study found younger age to be associated with subjective change three months after psychosomatic hospitalization ( 26 ), a second observational study ( N = 1829) found age not be associated with changes in psychological outcomes at admission, discharge, and 1-year follow-up ( 27 ). Similarly, though a RCT ( N = 298) of standardized five-week multimodal cognitive-behavioral therapy (CBT) demonstrated that women with depressive disorders and chronic pain syndromes benefit significantly more than men from the program ( 28 ), white men responded more robustly to a CBT intervention than other subgroups in a different study ( N = 2481) investigating a treatment effects of CBT in patients with minor or major depression after myocardial infarction ( 29 ). Furthermore, comorbid physical diseases, lower self-efficacy, and the number of mental disorders were found to be predictors of treatment outcomes (e.g., subjective complaints and negative mood) assessed at 1-year follow-up after inpatient psychosomatic treatment ( 27 ).…”
Section: Introductionmentioning
confidence: 99%